FIELDBUS INTEROPERABILITY TESTING AND SYSTEM CONFIGURATION - YOSRY MOHAMED MOHAMED, AHMED (UNIVERSITI TEKNOLOGI PETRONAS, 2009)
This report discusses the progress that has been done and the results from Foundation Fieldbus interoperability testing for Honeywell Host. The project work is in line with UTP team and PETRONAS Group Technology Solutions(PGTS) initiatives in FFIT. There are four vendors who supplied and installed the field bus system in the laboratory: Emerson, Honeywell, Foxboro & Yokogawa. But the author will only focus on segment 1 by using the Honeywell system. The main target of this project is to apply the basic interoperability tests for the system including device commissioning, decommissioning, online device replacement & calibration function checks, plus developing a plant model based on the test results as a step towards efficient real life application. This will give a better understanding of the Foundation Fieldbus system, elaborating strength and weakness points in the system, so this information and results could be implemented in PETRONAS’ Plants with absolute effectiveness. The tests are completed and the results will be recorded for future reference by PETRONAS. Also a plant model is done using a transmitter form segment 1. All the results from the test will be discussed and analyzed by the author in the next chapters.